PENANGANAN PENGEMBANGAN KARIR KARYAWAN BERDASARKAN PENGALAMAN KERJA DI FOOD AND BEVERAGE SERVICE NIRWANA GARDENS RESORT BINTAN-LAGOI - Repi Januardi; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The aims of study are determine (1) Handling employee career development based on work experience at food and beverage service Nirwana Gardens Resort Bintan Lagoi; (2) Efforts to improve employee career development in food and beverage service of Nirwana Gardens Resort Bintan-Lagoi.The design of this research is qualitative. The subjects of this research are the key informants, the Human Resourcess Manager Department and the additional informants are Assistant Outlet Manager and Employee of food and beverage service. Data collection techniques used are observation, documentation, and in-depth interviews. Data analysis techniques refer to the Milles and Huberman (1992) concepts.The research results show the handling of employee career development based on work experience in food and beverage service of Nirwana Gardens Resort Bintan Lagoi such as Job anlargement, Job Position, Job Rotation, Downwarkmove, Externship has not been implemented maximally and is situational, s should management to handle career development based on work experience will be better Sustainable because it gives a big impact on the company and employment, bias dig deeper potentials and provide opportunities to advance in the career. And efforts to improve employee career development are (1) Career Guidance should be given to the first employee to enter the company so that from the beginning already know the direction and career goals are not utuk employees who promoted aja; (2) Employee training is only for employees who enter the shift only, so that employees who do not enter or different shift can not be an opportunity to attend the training.Keywords : Employee Career, Work Experience, Resort